2019
DOI: 10.18310/2446-4813.2019v5n1p115-125
|View full text |Cite
|
Sign up to set email alerts
|

A percepção da equipe multiprofissional acerca do cuidado interdisciplinar em uma Unidade de Terapia Intensiva de Salvador-Bahia

Abstract: Objetivo: Avaliar a percepção dos profissionais de unidade de terapia intensiva sobre o cuidado interdisciplinar no seu cenário de atuação. Métodos: Este é um estudo de caráter exploratório com abordagem qualitativa, realizado em um Centro de Terapia Intensiva Adulto em Salvador-Bahia. A população analisada foi a equipe multiprofissional – nível superior e técnico – da referida unidade, selecionada aleatoriamente num dia e turno. Foram entrevistados sete indivíduos; posteriormente, o conteúdo das entrevistas f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
1
0
1

Year Published

2024
2024
2024
2024

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(2 citation statements)
references
References 0 publications
0
1
0
1
Order By: Relevance
“…With the findings, it was demonstrated that nursing care in the ICU is essential for critical user rehabilitation, emphasized by professionals on the importance of the entire team’s participation during the exposure of technologies for development, with joint action of knowledge. Formal and informal structures were created to manage demands, collaboratively, in line with comprehensive and resolute assistance, which presupposes actions of respect and support ( 21 , 22 ) . Thus, the concepts of hierarchy and subordination were balanced in favor of improving care, with articulation of knowledge, actions and services.…”
Section: Discussionmentioning
confidence: 99%
“…With the findings, it was demonstrated that nursing care in the ICU is essential for critical user rehabilitation, emphasized by professionals on the importance of the entire team’s participation during the exposure of technologies for development, with joint action of knowledge. Formal and informal structures were created to manage demands, collaboratively, in line with comprehensive and resolute assistance, which presupposes actions of respect and support ( 21 , 22 ) . Thus, the concepts of hierarchy and subordination were balanced in favor of improving care, with articulation of knowledge, actions and services.…”
Section: Discussionmentioning
confidence: 99%
“…Com os achados, demonstrou-se que o cuidado de enfermagem na UTI é essencial para a reabilitação do usuário crítico, enfatizado pelos profissionais sobre a importância da participação de toda a equipe durante a exposição das tecnologias para desenvolvimento, com atuação conjunta dos saberes. Criaram-se estruturas formais e informais para gerenciar as demandas, de forma colaborativa, em consonância com a assistência integral e resolutiva, que pressupõe ações de respeito e apoio (21)(22) . Assim, as concepções de hierarquia e subordinação foram equilibradas em prol da melhoria do cuidado, com articulação dos saberes, ações e serviços.…”
Section: Discussionunclassified